Controlled Zn(II) to Co(II) Transmetalation in a Metal–Organic Framework Inducing Single-Ion Magnet Behavior - Paula Escamilla; Nicolás Moliner; Donatella Armentano; Emilio Pardo; Jesús Ferrando-Soria; Thais Grancha (Magnetochemistry)
The intrinsic characteristic features of metal–organic frameworks offer unique, great opportunities to develop novel materials with applications in very diverse fields. Aiming to take advantage of these, the application of post-synthetic methodologies has revealed itself to be a powerful approach to the isolation and structuration of metal ions, molecules, or more complex species, either within MOF channels or reticulated at their network, rendering novel and exciting MOFs with new or improved functionalities. Herein, we report the partial post-synthetic metal exchange of Zn(II) metal ions by Co(II) ones in water-stable three-dimensional CaZn6-MOF 1, derived from the amino acid S-methyl-L-cysteine, allowing us to obtain two novel MOFs with increasing contents of the Co(II) ions Co4%@1 and Co8%@1. Remarkably, the presented post-synthetic metal exchange methodology has two relevant implications for us: (i) it allowed us to obtain two novel MOFs, which were not accessible by direct synthesis, and (ii) enabled us to transform physical properties within this family of isoreticular MOFs from the diamagnetic pristine MOF 1 to MOFs Co4%@1 and Co8%@1, exhibiting field-induced, frequency-dependent, alternating current magnetic susceptibility signals, which are characteristic features of single-molecule magnets.